2019
DOI: 10.1016/j.omtn.2018.10.017
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b Mediates Lung Mesenchymal-Epithelial Transition and Prevents Lung Fibrosis in the Silicosis Model

Abstract: Lung epithelial-mesenchymal transition (EMT) plays an important role in silicosis fibrosis. The reverse process of EMT is mesenchymal-epithelial transition (MET), which is viewed as an anti-EMT therapy and is a good target toward fibrosis. MicroRNAs (miRNAs) have emerged as potent regulators of EMT and MET programs, and, hence, we tested the miRNA expression using microarray assay and investigated their roles in silica-induced EMT in lung epithelial cells. We found that miRNA-29b (miR-29b) was dynamically down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…An in-depth study of EMT contributes to understanding the mechanism of silicosis. Considering that TGF-β1 could strongly induce EMT, 10,11 we establish a EMT cell models using TGF-β1 stimulated A549 cells, and found that the epithelial maker E-cad has a reduced expression and mesenchymal markers vimentin and α-SMA have a relatively increased expression which are in line with expectations.…”
Section: Discussionsupporting
confidence: 77%
“…An in-depth study of EMT contributes to understanding the mechanism of silicosis. Considering that TGF-β1 could strongly induce EMT, 10,11 we establish a EMT cell models using TGF-β1 stimulated A549 cells, and found that the epithelial maker E-cad has a reduced expression and mesenchymal markers vimentin and α-SMA have a relatively increased expression which are in line with expectations.…”
Section: Discussionsupporting
confidence: 77%
“…Bi WR et al [18] proposed that bone morphogenetic protein-7 could induce down-regulation of 1α-SMA mRNA and up-regulation of E-cadherin mRNA, which could promote the transformation of EMT to mesenchymal-epithelial transition (MET) in rat hepatocyte, thereby reducing liver fibrosis. Sun et al [19] confirmed that miRNA-29b could inhibit EMT induced by silica in RLE-6TN cells and promote MET. More and more researchers believe that endometrial EMT may be one of the main mechanisms of IUA [35].…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of the mir-29 family members is associated to enhanced fibrosis in various organs, whereas their induction (forced overexpression or drug-mediated) results in fibrosis inhibition. A recent study, in mice, has demonstrated the role played by mir-29b as an EMT inhibitor in lung fibrosis induced by silica, underlining the possible therapeutic use of mir-29 for silicosis ( Liu et al, 2010 ; Sun et al, 2019 ). The precise mechanism of this anti-fibrotic activity is still under investigation, nevertheless, the mir-29 family seems to have a series of targets, from TIMP1 (that inhibits the MMPs and ECM degradation), to PDGFR (the receptor for PDGF, a key fibrotic mediator), that end in an anti-fibrotic effect.…”
Section: Emt and Other Molecular Mediators Of Fibrosismentioning
confidence: 99%